Pengaruh Waktu Hidrotermal Terhadap Sifat Optik Nanokomposit Fe3O4@CQD (Carbon Quantum Dots) - Putri Azima Rafsanjani; Astuti Astuti (Universitas Andalas, 2025)
This study aims to synthesize Fe₃O₄@CQD nanocomposites using a hydrothermal method with time variations to study their effects on the structural and optical properties of the material. Fe₃O₄ nanoparticles were obtained through a coprecipitation method, while CQDs were synthesized from the extract of sappan wood (Caesalpinia sappan L.) which is natural, environmentally friendly, and has the potential as a fluorescent material. The results of XRD characterization showed that Fe₃O₄ has a crystal size of 22.476 nm, while the addition of CQDs increased the crystal size of the nanocomposite. FTIR analysis confirmed the presence of typical functional groups such as Fe–O, O–H, C–H, and C=O indicating the presence of CQDs in Fe₃O₄. UV-Vis test shows that Fe₃O₄@CQD has an absorption peak in the wavelength range of 300-700 nm, while the fluorescence test shows that the emission intensity increaseswith increasing hydrothermal time, with the emission peak at a wavelength of 600–650 nm.